Policy impact on stakeholder benefits and resource use and conservation in Mozambique : the case study of Moflor Forest Concession Area and Pindanganga Community Area - Falcao, Mario Paulo Pereira da Silva (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2005.